Evolution Sustainable Green Inner-wall with Flexible Floor Plan - Tawil, N.M.; Hussaini, H. A.; Basri, H.; Ani, A. I. Che; Mydin, M.A.O (EDP Sciences, 2014)
The trend of renovate residential houses especially the interior of the house has become a common phenomenon for homeowners nowadays in Malaysia. This scenario is quiet concern because sometimes no modifications to comply with the law and the guidelines set by the government housing. Modifications with not done properly can cause injury and harm to families and the people around. To reduce this problem, the concept of sustainable inner walls with flexible floor plan should be incorporated in every house in Malaysia. This is because the wall is the basic structure of a building and usually serves as the border, supporting structures and dividing the space with another space. Wall also causes an increase of the price of a house. This is due to the increase in raw material costs and labor costs, land subsidence have to bear by the developer. The increasing in house prices is causing among Malaysians, especially young executives cannot afford to buy their first home. To reduce the price of the home, reduction in construction interior wall in wet construction should be done and replaced with the sustainable inner wall. This sustainable inner wall also can save the space and the owner simplify can added or reduced the room according their need without spending too much money for renovation in the future.